The V-one-V Construction and Modification of the Verbal Domain in Cantonese - Lam Charles (Sciendo, 2020)
This study deals with a syntactic analysis of the V-one-V construction that has implications on the structure of verbal modification in Cantonese. The V-one-V construction is unique in several ways, making it distinct from the cognate object construction in English or the verb-doubling construction in Cantonese. Several syntactic and semantic properties are discussed that support a syntactic analysis of V-one-V as an instance of syntactic verb copying (Corver and Nunes 2007) rather than a morphological treatment often prescribed to reduplication. The V-one-V construction consists of two copies of a verb with a number or quantifier jat1 ‘one’, loeng5 ‘two’, or gei2 ‘few’ between the copies. The construction denotes the delimitation of events, displaying interpretations of tentative, brief occurrences of events. This pattern indicates that V-one-V denotes delimitation in the senses of both counting and measuring and the choice depends on the nature of the VP, according to the data. This study also contributes to the discussion on postverbal modification as an alternative to V-one-V, which is more productive in its meaning and lexical choice.